PFKFB3: A Potential Key to Ocular Angiogenesis - Zhou, Zi-Yi; Wang, Lin; Wang, Yu-Sheng; Dou, Guo-Rui (Frontiers in Cell and Developmental Biology, 2021)
The current treatment for ocular pathological angiogenesis mainly focuses on anti-VEGF signals. This treatment has been confirmed as effective despite the unfavorable side effects and unsatisfactory efficiency. Recently, endothelial cell metabolism, especially glycolysis, has been attracting attention as a potential treatment by an increasing number of researchers. Emerging evidence has shown that regulation of endothelial glycolysis can influence vessel sprouting. This new evidence has raised the potential for novel treatment targets that have been overlooked for a long time. In this review, we discuss the process of endothelial glycolysis as a promising target and consider regulation of the enzyme 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase as treatment for ocular pathological angiogenesis.